(The Processing of Aloe Vera in Syrup and Techno-Economic Analysis for Its Small Scale Industry) - Sapto Hartanto, Eddy Sapto Hartanto; Djubaedah, Endah; Hawani Lubis, Enny (Balai Besar Industri Agro, 2003)
There are many useful of aloe vera plant such as traditional medicine,cosmetics,foods and beverage industry .the study of aloe vera in syrup production has been conducted. time of steaming process (a)and sugar adding (b) were used as factor treatment .the variation of those factors was 5minutes (a1),10 minutes (a2) and 15 minutes (a3) for time of steaming proces while 20% (b1),25%(b2)and 30%(b3) of sugar adding .the result of panel test showed that the best treatment which had the highest score in taste (600),appearance (642) and elasticity (6.20) was a2b2 treatment product,which conducted on 10 minutes steaming process and 25% of sugar adding .the product was analyzed in accordance contaminat,presrvative agent,total plate count (TPC)colifrom and mould after 12 weeks storage ,the product in ambient as well as in cooling temperature still met SNI of product in syrup.the result of techno-economic showed that the small industry of 1000-1500 cup per day capasity was feasible financially with pay back period in 3-4 years.Â